Variation in Sensory Attributes and Volatile Compounds in Beers Brewed from Genetically Distinct Malts: An Integrated Sensory and Non-Targeted Metabolomics Approach. (2nd April 2020) - Bettenhausen, Harmonie M.; Benson, Amanda; Fisk, Scott; Herb, Dustin; Hernandez, Javier; Lim, Juyun; Queisser, Sue H.; Shellhammer, Thomas H.; Vega, Veronica; Yao, Linxing; Heuberger, Adam L.; Hayes, Patrick M.
Abstract: Previous research demonstrates that barley genetics can influence beer flavor. However, the chemical basis for differences in beer flavor attributed to barley is not well defined. Here, the associations between beer volatile compounds and sensory descriptors were investigated in a controlled experiment, whereby barley genotype was the main driver of variation in the system. Beer was brewed from three advanced barley breeding lines and compared to a CDC Copeland control. Sensory studies were performed via three independent panels (a consumer, brewery, and laboratory panel). The results suggest that the four beer samples have distinct flavor profiles that could be discriminated by the three sensory panels. Volatile compounds for the four beers were characterized using HS/SPME-GC-MS; quantitation and annotation were performed using a non-targeted metabolomics approach on 397 detected compounds. The O2PLS data analysis supports that alkane/alkenes, benzenoids, amides/amines, and fatty acid esters were associated with the most desirable lager traits, compared to Maillard Reaction Products that were more abundant in the beers with "non-ideal" lager traits. Taken together, these data further support the role of barley genetics in beer flavor and provide new information on the types of volatile metabolites that can vary in controlled systems.